Sexual dimorphism of stress response and immune/ inflammatory reaction: the corticotropin releasing hormone perspective - Vamvakopoulos, Nicholas V. (Hindawi Publishing Corporation, 1995)
This review higlghts key aspects of corticotropin releasing hormone (CRH) biology of potential relevance to the sexual dimorphism of the stress response and immune/inflammatory reaction, and introduces two important new concepts based on the regulatory potential of the human (h) CRH gene: (1) a proposed mechanism to account for the tissue-specific antithetical responses of hCRH gene expression to glucocorticolds, that may also explain the frequently observed antithetical effects of chronic glucocorticoid administration in clinical practice and (2) a heuristic diagram to illustrate the proposed modulation of the stress response and immune/ inflammatory reaction by steroid hormones, from the perspective of the CRH system.